The reality of the territorial governance in the Moroccan mountainous regions: the Tichoukt Massif as case of study: واقع الحكامة الترابية بالمناطق الجبلية المغربية: كتلة تيشوكت نموذجا - محمد , أوشرو; يوسف , بالحاج (African Scientific Journal, 2021)
Abstract The Moroccan mountains offer unique zones of biological and cultural diversity, yet most of their inhabitants suffer from poverty and vulnerability, and their ecosystems are highly vulnerable to natural hazards and environmental degradation. This research paper attempts to shed light on the role of actors in establishing a governance model that considers the peculiarities of development in mountainous regions. It further highlights the importance that governance has become in the process of evaluating territorial management as well as its role in managing development in the Moroccan mountain areas in general, while focusing on the Tichoukt massif in particular, as it is an integral part of the Moroccan mountain system. We therefore adopted a field study in which we worked on an inventory of the actors directly concerned with development at the massif level, whether at the local, provincial or regional level, defining their roles, goals and strategies, and understanding the structure of the relationships between them and then evaluate its implications on the reality of territorial governance in the field of study. Accordingly, the results of the field study analysis showed us that the mountain regions in general, and the Tichoukt massif in particular, lack basic actors capable of coordinating the interventions of the rest of the actors in the field of development, and that their positions do not correspond with the broad powers granted to them by the Constitution and the Charter of Administrative Decentralization. Keywords : territorial governance, actors, Tichoukt massif, strategies, territorial foresight. ملخص: تقدم الجبال المغربية مجاالت فريدة من التنوع االحيائي والثقافي، اال أن معظم سكانها يعانون من الفقر والهشاشة، كما أن النظم االيكولوجية بها معرضة بشكل كبير للمخاطر الطبيعية والتدهور البيئي. تحاول هذه الورقة البحثية تسليط الضوء على دور الفاعلين في ترسيخ نموذج حكامة يراعي خصوصيات التنمية بالمناطق الجبلية، نظرا الى األهمية التي أصبحت تحظى بها الحكامة في عملية تقويم التدبير الترابي، ودورها في تدبير التنمية بالمجاالت الجبلية المغربية عموما، وكتلة تيشوكت بشكل خاص، باعتبارها جزء ال يتجزأ من المنظومة الجبلية المغربية. لتحقيق هذا الغاية، اعتمدنا دراسة ميدانية، عملنا فيها على جرد الفاعلين المعنيين مباشرة بالتنمية على مستوى الكتلة، سواء على المستوى المحلي أو المستويين اإلقليمي والجهوي، وتحديد أدوارهم وأهدافهم واستراتيجياتهم، ومعرفة بنية العالقات التي تربط بينهم. ومن تم تقييم انعكاساتها على واقع الحكامة الترابية بمجال الدراسة. بناء عليه أظهرت لنا نتائج تحليل الدراسة الميدانية، أن المناطق الجبلية بصفة عامة والكتلة بشكل خاص تفتقد إلى فاعلين أساسين قادرين على القيام بعمليات تنسيق تدخالت باقي الفاعلين في مجال التنمية، وأن مواقعهم ال تتالءم والصالحيات الواسعة التي منحها لهم الدستور وميثاق الالتمركز اإلداري. الكلمات المفاتيح: الحكامة الترابية، الفاعلون، كتلة تيشوكت، االستراتيجيات، االستشراف الترابي.